Improving Student Learning Outcomes Through Hindu Interactive E-Modules - I Ketut Septiyan Kurniawan; Alexander Hamonangan Simamora (Jurnal Edutech Undiksha, 2023)
The low learning outcomes of students learning Hinduism are due to the need for more interactive and interesting learning media for students. This study aims to describe the design and quality of the results of the validity of the Religious Interactive E-Module. This research belongs to the development research developed using a 4-D model with the stages of defining, designing, developing, and deploying. The subjects involved in this study were one subject matter expert, one instructional design expert, one instructional media expert, three students for individual trials, and nine students for small group trials. Data was collected using interviews, document recordings, and questionnaires with research instruments in the form of subject content expert instruments, design experts, instructional media experts, and individual trials. The data analysis used is a qualitative descriptive analysis technique. The results of the research analysis showed that the Interactive Hindu Religion E-Module was declared valid, with the results of a review by subject content experts indicating that the Hindu Religion Interactive E-Module had a very good rating (100%). The results of the expert review of the Interactive E-Module learning media show that the product has a good rating (87%). The review results by the learning design experts showed that the Interactive E-Module of Hindu Religion had an adequate rating (68%). Individual test results show that the Interactive E-Module has a good rating (92.3%). The results of the small group test showed that the E-Module had a very good rating (93.58%). It means that the Interactive E-Module in Hinduism is proven to be of good quality and is suitable for use in the learning process of Hinduism.